PENDIDIKAN NASIONAL PARIWISATA TERHADAP PENGEMBANGAN DAN TANTANGAN DUNIA PARIWISATA (Jurnal Ilmiah Pariwisata, 2014)
Tourism development should be supported by qualified human resources, so that the development can be carried out on an ongoing basis and in accordance with the needs of the community. Improving the quality of eduaction is a matter that is not negotiable so that we can competence with foreign graduates (developed countries) is to implement a management system that is both educational and professional. With KKNI reflect the learning outcomes obtined one can through: (1) educatin; (2) training; (3) work experience, and (4) self-learning, so that would change how I view someone's competence, which is no longer solely on the diploma but with a view to the agreed framework of national qualifications as the basis for the recognition of one's educational outcomes widely (formally, non-formal, in formal or self-taught) are accountable and transparent.Institutional arrangement can be done by implementing a quality system of higher education "profesioinal" tourism that allows its graduates meet the qualification standards applied by the industry skills. Qualifications desired standards can be obtained from the "color" of a college, which owns the foundation of planning and implementation of educational programs and local curriculum-based culture of excellence, where "color" is derived from input from business / industry, students, parents of students , staff (teaching and administrative), alumni, as well as the development of information technology.